2007
DOI: 10.1007/s11664-006-0044-x
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Photoelectron Spectroscopy Characterization of Aluminum Nitride Surface Oxides: Thermal and Hydrothermal Evolution

Abstract: Oxidized surfaces of aluminum nitride (AlN) epilayers grown on sapphire substrates and of AlN bulk crystals grown by physical vapor transport were studied by x-ray photoelectron spectroscopy (XPS). Analysis of the oxygen core level spectra showed approximately equal contributions from oxygen in two bonding states, which were identified by the binding energies and relative separation of the fitted peaks as OH ) and O 2) . The oxide on air-exposed AlN surfaces was identified as aluminum oxide hydroxide. Systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
44
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 19 publications
4
44
0
Order By: Relevance
“…In this case, the reactions might involve (1) 2Al(OH) 3 25 supports the probability of reactions 1 and 2 occurring. Similar conclusions were drawn from XPS analysis by Dalmau et al; 19 an oxygen peak characteristic of a hydroxide was reduced by annealing for 6 h from 260 °C to 830 °C under ultrahigh vacuum. The intensity of XPS oxygen peaks changed in a manner indicating a shift in the surface composition from AlOOH toward Al 2 O 3 with increasing temperature.…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…In this case, the reactions might involve (1) 2Al(OH) 3 25 supports the probability of reactions 1 and 2 occurring. Similar conclusions were drawn from XPS analysis by Dalmau et al; 19 an oxygen peak characteristic of a hydroxide was reduced by annealing for 6 h from 260 °C to 830 °C under ultrahigh vacuum. The intensity of XPS oxygen peaks changed in a manner indicating a shift in the surface composition from AlOOH toward Al 2 O 3 with increasing temperature.…”
Section: Introductionsupporting
confidence: 85%
“…18,19 Its formation occurs rapidly, within a few minutes. Panchula and Ying 18 followed the formation of native hydroxides on freshly prepared nanocrystalline AlN upon exposure to oxygen and water vapor in ambient air by photo-acoustic Fourier transform infrared spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results have been reported by Ansart et al 26 who concluded that no chemical alterations of AlN deposited with plasma-enhanced CVD took place below 850 C in air and that transformation to a-Al 2 O 3 took place rapidly above 1100 C in air. Dalmau et al 27 reported AlN to form a thin layer ($1 nm) of AlOOH at room temperature under ambient-air exposure. This layer then approached the stoichiometry of Al 2 O 3 when annealed under vacuum in higher temperatures.…”
Section: Introductionmentioning
confidence: 99%